A Green Approach for High Oxidation Resistance, Flexible Transparent Conductive Films Based on Reduced Graphene Oxide and Copper Nanowires - Ya-Ting Lin; Da-Wei Huang; Pin-Feng Huang; Li-Chun Chang; Yi-Ting Lai; Nyan-Hwa Tai (Nanoscale Research Letters, 2022)
Abstract Copper nanowires (CuNWs)-based thin film is one of the potential alternatives to tin-doped indium oxide (ITO) in terms of transparent conductive films (TCFs). However, the severe problem of atmospheric oxidation restricts their practical applications. In this work, we develop a simple approach to fabricate highly stable TCFs through the dip-coating method using reduced graphene oxide (rGO) and CuNWs as the primary materials. Compared with previous works using toxic reduction agents, herein, the CuNWs are synthesized via a green aqueous process using glucose and lactic acid as the reductants, and rGO is prepared through the modified Hummers’ method followed by a hydrogen-annealing process to form hydrogen-annealing-reduced graphene oxide (h-rGO). In the rGO/CuNWs films, the dip-coated graphene oxide layer can increase the adhesion of the CuNWs on the substrate, and the fabricated h-rGO/CuNWs can exhibit high atmospheric oxidation resistance and excellent flexibility. The sheet resistance of the h-rGO/CuNWs film only increased from 25.1 to 42.2 Ω/sq after exposure to ambient atmosphere for 30 days and remained almost unchanged after the dynamic bending test for 2500 cycles at a constant radius of 5.3 mm. The h-rGO/CuNWs TCF can be not only fabricated via a route with a superior inexpensive and safe method but also possessed competitive optoelectronic properties with high electrical stability and flexibility, demonstrating great opportunities for future optoelectronic applications.